Berberine attenuates renal injury in rats with chronic renal failure - XIE Dandan, LI Han, WANG Baiju, WANG Na, CHEN Hanwen, LIU Lei (Jichu yixue yu linchuang)
Objective To investigate the effect of berberine (BBR) on chronic renal failure (CRF) rats and its mechanism. Methods CRF rat model was established by removing 5/6 kidneys and all rats were randomly divided into sham group, chronic renal failure model group, berberine treatment group and uremic clearance granules (UCG) treatment group with 10 in each. Renal function indexes in each group were examined by an automated biochemistry instrument. The level of MMP-2 and MMP-9 were detected by ELISA. The degree of renal fibrosis was observed by PAS and Masson staining microscopy. The expression of NF-κB p65 and IL-6 were detected by immunohistochemistry method. Expression of fibrosis-related proteins and TGF-β1/ERK signaling pathway proteins in renal tissues was detected by Western blot. Results Compared with sham group, renal function and renal histopathological damage was significantly increased in the model group, and BBR improved renal function and histopathological damage in CRF rats. Compared with the sham group, the serum level of MMP-2 and MMP-9 was significantly decreased (P＜0.05), the expression of IL-6 and NF-κB p65 was up-regulated (P＜0.05). The expression of FN, α-SMA, Col-Ⅰ, Col-Ⅲ, TGF-β1, and p-ERK1/2 proteins was up-regulated in the model group of rats(P＜0.05), while the BBR treatment significantly reversed the expression of these molecules (P＜0.05). Conclusions BBR may improve inflammation and fibrosis by inhibiting TGF-β1/ERK1/2 pathway, and play a protective role in the kidney of CRF rat.